Edge-event-triggered encryption-decryption observer-based control of multiagent systems for privacy protection under multiple cyber attacks - Guo, Xiang-Gui; Wang, Bo-Qun; Wang, Jian-Liang; Ahn, Choon Ki; Wu, Zheng-Guang (Information sciences, 2023)
This study investigates the secure and privacy-preserving consensus problem for a class of Lipschitz nonlinear multiagent systems (MASs) under undirected topology and multiple cyber attacks. An observer-based dynamic cryptography-based encryption-decryption (CED) pairing algorithm is proposed to achieve privacy preservation and defend against replay attacks simultaneously. To reduce the computation and communication resources and facilitate paired password design, a Zeno-free edge-event-triggered mechanism (EETM) based on edge (rather than neighbor) information is developed in a completely distributed manner, using only local observation information without any knowledge about the global topology. The designed EETM can accommodate multiple event-triggered functions, which simplifies the EETM design procedure. Interestingly, the CED pairing algorithm makes the effect of replay attacks equivalent to that of denial-of-service (DoS) attacks. Thus, DoS and replay attacks can be handled as the same types of attacks. In addition, a resilient EETM-based control strategy against DoS and replay attacks is proposed to make the MAS reach consensus faster, within the attack sleep time. Furthermore, sufficient conditions for the frequency and duration of replay and DoS attacks are established to achieve secure consensus of the MAS. Finally, a numerical example is provided to demonstrate the validity and superiority of the proposed method.